QUALITY OF POPULATION ADMINISTRATION SERVICES AT THE OFFICE OF THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN THE CITY OF GORONTALO - Tome, Falmawati; Igirisa, Irawaty; Kamuli, Sukarman (Public Policy Journal, 2024)
This study aims to determine the Quality of Population Administration Services at the Office of the Population and Civil Registration Office in Gorontalo City. The research method used is qualitative research. Data collection techniques used are observation techniques, interviews, and documentation. The results of this study indicate tangible, reliability, responsiveness, assurance, and empathy. (1) the implementation of service quality related to the tangible dimension (physical evidence) has not fulfilled adequate service facilities in the Gorontalo city population and civil registration office such as narrow waiting rooms, limited seats, and lack of air conditioning. (2) The dimension of employee reliability in dealing with community problems, it can be seen that there are still complaints from the public about the service process and population administration. (3) the dimension of responsiveness of employees has shown responsiveness in helping the community when experiencing difficulties (4) the dimension of assurance (guarantee), being on time for community services, it can be seen that there are still public complaints. (5) the dimension of empathy (empathy), has been running quite well because the employees have technical guidance that is carried out in carrying out services every year. Based on this analysis, researchers can conclude that the quality of population administration services at the Gorontalo City Population and Civil Registration Office is quite good. Based on this, the researchers hope that in the future the facilities and infrastructure can be improved and even better, as well as for employees to further improve the quality of work.